REFORMAS AL CÓDIGO ORGÁNICO DE LA FUNCIÓN JUDICIAL PARA APLICAR EL PRINCIPIO DE LA ESPECIALIZACIÓN EN LA ADMINISTRACIÓN DE JUSTICIA EN LA SUSTANCIACIÓN DE LAS GARANTÍAS JURISDICCIONALES - Padilla Padilla, Lenin Vicente (2015)
The Constitution of the Republic of Ecuador establishes the jurisdictional guarantees as a mechanism through which the State guarantees the observance of fundamental rights of persons recognized in the Constitution, international legal instruments on human rights and legal norms in the country, and determines that the Constitutional Court is the highest body of justice in constitutional matters, establishing in this way the principle of specialty, which is enshrined in the Organic Code of the Judiciary, as a way to ensure security legal persons subject to trial, based on the certainty that justice administrators have specific knowledge about the subject on which resolved. Despite the validity of the principle of specialty in both constitutional law and which regulates the activity of the judiciary in Ecuador, the Organic Law of Judicial Guarantees and Constitutional Control determines that any trial judge is competent to hear processes related to judicial guarantees, thereby affecting the performance of the invoked principle, as important as is the constitutional law and constitutional procedural law, which are effective mechanisms for guaranteeing the fundamental rights of individuals subject. Therefore a legal issue, which is the focus and study in a comprehensive manner in this work, entitled materializes: "AMENDMENTS TO ORGANIC CODE OF JUDICIAL FUNCTION TO IMPLEMENT THE PRINCIPLE OF EXPERTISE IN THE ADMINISTRATION OF JUSTICE IN THE CONDUCT OF JUDICIAL 5 GUARANTEES”. The work is based on a broad theoretical argument that includes conceptual, doctrinal, legal and comparative law content, and results obtained by applying the techniques of research, which confirm the existence of the problem studied, and serve to draw conclusions and recommendations, and finally realize a legal proposal for reform to help ensure that the principle of specialty, in the conduct of judicial guarantees, as a means to protect the right to legal security and fundamental rights citizens